Role of Smartphone Addiction in Instigating Phubbing Behavior: Perspective of the University Students in Multan City, Pakistan - Ismail, Tayyaba; Sattar, Tehmina; Ullah, Muhammad Imdad; Ahmad, Rashid; Zafar, Ehtisham (Pakistan Journal of Humanities and Social Sciences, 2025)
Phubbing is a socio-psychological phenomenon of turning a blind eye to interpersonal relationships and networking with long-distance friends. The salient underlying reasons behind phubbing behavior are to line up online interaction with distant people, constantly check notifications/updates on mobiles, and divert from real-life situations. Consequently, the people feel lonely, isolated, ignored, impaired, and disrespected by the phubber. The noteworthy theoretical underpinnings of the present study were i) Media dependency theory, accompanied by ii) The uses and gratification theory. Data was collected from N=400 university students through a self-administered questionnaire. Using a multistage sampling technique, the students were approached through a survey method for data collection. Afterward, the data was analyzed through SPSS (version 25). Results of the study illustrated that smartphones played a domineering role in instigating the phubbing behavior among university students with high correlation, i.e., r=0.939** to 0.984**, and significant regression, i.e., 75.6%. Vigilance of faculty members and university administration, complemented by parental monitoring, can lessen the screen timings of the students to curb their phubbing behavior.